A Novel Nano-Surfactant NiFe2O4-Chitosan Nanoparticles Composed and Used in Enhanced Oil Recovery - Lian, Q.; Zheng, X.F. (Asian Journal of Chemistry, 2014)
Different from the traditional surfactants, the novel magnetic NiFe2O4-chitosan nanoparticles has the advantage of excellent biodegradation and a high level of controllability. The NiFe2O4- chitosan nanoparticles with core-shell structure was prepared successfully. The images of TEM and the SEM showed that the cubic-shape magnetic NiFe2O4 particles were encapsulated by the spherical chitosan nanoparticles. The size of the NiFe2O4 -chitosan nanoparticles were all below 100 nm. The saturated magnetization of the NiFe2O4 -chitosan nanoparticles could reach 75 emu/g and showed the characteristics of superparamagnetism at the same time. The evaluation on the interfacial properties of the product showed that the interfacial tension between crude oil and water could be reduce to ultra-low values as low as 10-3 mN/m when the magnetic NiFe2O4- chitosan nanoparticle was used in several blocks in Shengli oilfield without other additives. Meanwhile, the magnetic NiFe2O4-chitosan nanoparticles possessed good salt-resisting capacity.